2021
DOI: 10.31436/ijohs.v2i1.55
|View full text |Cite
|
Sign up to set email alerts
|

The use of bioceramic root canal sealers for obturation of the root canal system: A review

Abstract: The use of bioceramic root canal sealers in endodontics is a promising approach because of the advantages such as improved flow properties, biocompatible and could promote the formation of hard tissue. Due to the recent technology and limited scientific evidence, the effectiveness of bioceramic root canal sealers remains unclear. This article focuses on the physicochemical properties, biocompatibility, biomineralisation, retreatability, 3D obturation and current practice of using bioceramic root canal sealers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…As in earlier studies that revealed that Bio-C Sealer showed higher flowability than Ceraseal (40,41) . Also, according to recent study, CeraSeal did not properly optimize the ANSI/ADA standardization of sealers flowability (42) . In contrast, AH Plus having larger size, so polymerization shrinkage or problems during mixing might diminish its permeability into the dentinal tubules, the mixing process of sealers might have a factor in the sealer penetration into dentinal tubules (13) .…”
Section: Discussionmentioning
confidence: 99%
“…As in earlier studies that revealed that Bio-C Sealer showed higher flowability than Ceraseal (40,41) . Also, according to recent study, CeraSeal did not properly optimize the ANSI/ADA standardization of sealers flowability (42) . In contrast, AH Plus having larger size, so polymerization shrinkage or problems during mixing might diminish its permeability into the dentinal tubules, the mixing process of sealers might have a factor in the sealer penetration into dentinal tubules (13) .…”
Section: Discussionmentioning
confidence: 99%
“…The term "amorphous precursor strategy" describes a method by which organisms fill pore spaces, manage crystallisation, and control the chemistry of the final CaCO3 polymorph by taking advantage of the flexibility of amorphous phases prior to crystallisation. The composition of natural waters, their alkalinity, and the solubility of other solid phases are all controlled by the dissolutionprecipitation cycling of CaCO3, which also controls the precipitation of a variety of minerals [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The increased fracture resistance could be due to its chemical bonding through the formation of hydroxyapatite crystals during the set when the material is in contact with moisture. The researcher designed this study to observe crystal formation in our novel CO3Ap endodontic sealer [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, their biocompatibility prevents rejection by the surrounding tissues andsecondly, bioceramic materials contain calcium phosphate which enhances the setting properties of bioceramics and results in chemical composition and crystalline structure similar to tooth and bone apatite. The main advantage of a premixed calcium-silicate root canal sealer consists of having a homogeneous mixture, irrespective of the alteration of powder/liquid ratio [21,22]. Physiochemical properties of root canal sealer have to provide an apical seal avoiding the leakage of irritants and pathogens from the root canal system into the peri-radicular tissues(visa-versa).…”
mentioning
confidence: 99%